Peran Kunci: Teknologi, Human Capital, dan FDI Terhadap Pertumbuhan Ekonomi dalam Teori Endogen - Andrawina, Kevin Eric; Rahayu, Siti Aisyah Tri; Hakim, Lukman (HUMANIORUM, 2024)
This research focuses on the role of technology, human capital, and foreign direct investment (FDI) on economic growth in ASEAN countries and China during the period 1999 to 2019. This research uses panel data regression analysis. The research results show that technology has a significant positive impact on economic growth. On the other hand, human capital and FDI have a significant negative impact on economic growth in ASEAN countries and China.